Faktor-faktor yang Mempengaruhi Keputusan Merevaluasi Aset Tetap - Jefriyanto, Jefriyanto (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study aims to determine the effect of leverage, liquidity, fixed asset intensity, and size of the company against the decision to revaluate fixed assets. The research was conducted at a manufacturing company listed on the Indonesia Stock Exchange in 2012 until 2016 as many as 550 units of analysis and the sample is collected by using purposive sampling technique which the samples were chosen selectively. By using logistic regression, the result of this research is fixed asset intensity and firm size have positive effect to revaluation decision. Liquidity and leverage have no effect on the decision to revalue fixed assets. The conclusions of this study are companies that have high fixed assets and companies with a large percentage of sales are more likely to revalue fixed assets.